Educational Technologies In A Personalised Learning Environment (PLE) : An Overview - Mohamad Nor, Azmawaty; Che Ku Mohd, Che Ku Nuraini; Shahbodin, Faaizah; Md Saad, Mohd Shamsuri; Mohamad, Siti Nurul Mahfuzah; Sa'aya, Zurina (WIETE, 2020)
A personalised learning environment (PLE) is focused on Web 2.0 tools as a way of integrating learning processes in a digital and technologically dynamic environment. The PLE helps in the preparation of future teachers to lead the way in the development of educational approaches that encourage knowledge building. The PLE represents a new, wide-ranging evolution in educational practices by integrating information and communications technology (ICT) applications to create wall-free schools capable of meeting the demands of the information society. In this article, the authors overview a range of PLE tools based on Web 2.0 technologies. The main aim is to assist in the transformation of learning and teaching in higher education, and to prepare learners for future work in a dynamic context with a high degree of digital and technological influence. The key findings could be used as instructions for PLS tools to facilitate structured learning by both teachers and students.